2019
DOI: 10.1002/2050-7038.12122
|View full text |Cite
|
Sign up to set email alerts
|

Using IEC 61850 GOOSE messages in microgrid protection

Abstract: Summary The conventional upstream/downstream protection coordination approach and master/slave information communication method in radial distribution network can no longer satisfy the protection requirement in a microgrid because the loads and distributed energy resources (DERs) have stochastic characteristics and the topology of a microgrid changes over time. In the proposed microgrid protection architecture, to have the intelligent protection intelligent electronic devices (IEDs) with IEC 61850 communicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Some previous studies addressed the construction of an experimental framework to approximate the IEC61850 standard [14] [15] [16], considering physical constraints while maintaining scalability, to ease the way for more complex power grid implementations. The authors in [15], investigated complex protection coordination using the Arcteq-F215 IED. Their work redefines the relationship between primary and backup protection for microgrid protection.…”
Section: Related Workmentioning
confidence: 99%
“…Some previous studies addressed the construction of an experimental framework to approximate the IEC61850 standard [14] [15] [16], considering physical constraints while maintaining scalability, to ease the way for more complex power grid implementations. The authors in [15], investigated complex protection coordination using the Arcteq-F215 IED. Their work redefines the relationship between primary and backup protection for microgrid protection.…”
Section: Related Workmentioning
confidence: 99%
“…The master‐slave controlled microgrid can operate independently from the utility grid, a U/f‐controlled IIDG (U/f‐IIDG) is used as the main source to maintain the voltage and frequency stability of buses, and PQ‐controlled IIDGs (PQ‐IIDGs) are used as slave sources to provide the power to a microgrid 4,5 . The plug‐and‐play characteristics of IIDGs change the topology of microgrid, with the result that the traditional fault analysis methods are no longer suitable for microgrids 6,7 . How to establish the fault models of master‐slave controlled microgrids and calculate the fault characteristics quantitatively are the issues to be solved for the microgrid protection.…”
Section: Introductionmentioning
confidence: 99%
“…e last one considers a redial network to coordinate the OC relays based on the Genetic and Particle Swarm Optimization. In [13], the researchers propose a method for the protection of the microgrid rely in the IEC 61850 GOOSE messages to overcome the coordination difficulties due to multiple power sources, and the proposed method has been verified by a testing system. Another study [14] suggested an adaptive method by changing the setting groups of the relays via binary input depending on DGs connection state, for only DGs close relays based on the proposed sensitivity matrix.…”
Section: Introductionmentioning
confidence: 99%